Coumarin and spirocyclopentenone derivatives from the leaves and stems of Murraya paniculata (L.) Jack. (April 2020) - Liang, Haizhen; Cao, Nankai; Zeng, Kewu; Zhao, Mingbo; Tu, Pengfei; Jiang, Yong
Abstract: Seven previously undescribed compounds, including five coumarins, (+/−)-murpanitin A and murpanitins B-D, and a pair of spirocyclopentenone enantiomers, (+/−)-murrayaspiroketone, along with 14 known coumarin derivatives were isolated from the leaves and stems of Murraya paniculata (L.) Jack . Their structures were elucidated on the basis of comprehensive analysis of 1D and 2D NMR and HRMS spectroscopic data, and the absolute configurations were assigned via calculated and experimental ECD data. Three compounds showed moderate inhibitory effects on nitric oxide production stimulated by lipopolysaccharide in BV-2 microglial cells with IC50 values of 53.2 ± 8.9, 57.7 ± 5.8, and 53.2 ± 4.4 μM, respectively. Graphical abstract: Seven previously undescribed compounds and 14 known coumarins were isolated from Murraya paniculata (L.) Jack. Three compounds showed inhibition against LPS-induced NO production in BV-2 microglial cells. Image 1 Highlights: Seven previously undescribed compounds were isolated from Murraya paniculata (L.) Jack. A pair of coumarin enantiomers with a 2-oxo-1, 3-dioxolane unit were resolved by chiral HPLC. A pair of rare spirocyclopentenone enantiomers were separated by chiral HPLC. Three compounds showed moderate inhibition on NO production.